2022
DOI: 10.1002/chem.202201081
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorescence Induction by Host‐Guest Complexation with Cyclodextrins – The Role of Regioisomerism and Affinity

Abstract: We present an in-depth investigation of cyclodextrin complexes with guest compounds featuring complexation-induced room temperature phosphorescence (RTP) in aqueous solution. Very interestingly, only the complexed regioisomers bearing lateral substituents on meta-position show RTP, whereas the stronger host-guest systems with para-substituted dyes show no RTP features. The reported systems were investigated regarding their complexation behavior in water using isothermal titration calorimetry and mass spectrome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 74 publications
(37 reference statements)
0
4
0
Order By: Relevance
“…Substituting one or more thiophenyl groups with electron‐withdrawing substituents, such as nitriles, forms highly efficient push‐pull systems. As we have shown before, para ‐nitrile substituted tetrathiophenols are still capable of AIP with lifetimes in the range of microseconds [12,18,26] . Apart from the number and type of functional groups on the peripheral rings, substitution pattern plays a decisive role in the emission properties as well.…”
Section: Introductionmentioning
confidence: 78%
See 2 more Smart Citations
“…Substituting one or more thiophenyl groups with electron‐withdrawing substituents, such as nitriles, forms highly efficient push‐pull systems. As we have shown before, para ‐nitrile substituted tetrathiophenols are still capable of AIP with lifetimes in the range of microseconds [12,18,26] . Apart from the number and type of functional groups on the peripheral rings, substitution pattern plays a decisive role in the emission properties as well.…”
Section: Introductionmentioning
confidence: 78%
“…As we have shown before, paranitrile substituted tetrathiophenols are still capable of AIP with lifetimes in the range of microseconds. [12,18,26] Apart from the number and type of functional groups on the peripheral rings, substitution pattern plays a decisive role in the emission properties as well. Feng and co-workers demonstrated that by varying the substitution pattern of the peripheral mercaptophenol in a nitrile-substituted asterisk, the emission could be tuned from AIP to fluorescence occurring both in solution and in the solid-state (SSSE).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, the previously mentioned selfassembled J-aggregates show a distinct emission band that has been the subject of several studies regarding their interesting intermolecular interactions. [22] Besides viscosity increase or temperature lowering, molecular rigidification inducing emerging emission can appear as a consequence of host-guest inclusion with cyclodextrins (CDs) [23,24] or after DNA hybridization. [25] Because in many cases, emission is not induced solely upon aggregation but through restriction of motion, Gierschner et al proposed the more proper name "solid-state luminescence enhancement" (SLE).…”
Section: Classic Luminescence Phenomenamentioning
confidence: 99%